Evaluation of Vasopressin for Vasoplegic Shock in Patients With Preoperative Left Ventricular Dysfunction After Cardiac Surgery: A Propensity-Score Analysis. Issue 5 (November 2018) - Cheng, Yongqing; Pan, Tuo; Ge, Min; Chen, Tao; Ye, Jiaxin; Lu, Lichong; Chen, Cheng; Zong, Qiuyan; Ding, Yi; Wang, Dongjin
ABSTRACT: Purpose: Postoperative vasoplegic shock after cardiac surgery seems to be a frequent complication with poor outcomes. We hypothesized that vasopressin may increase the risk of poor outcomes in patients with preoperative Left Ventricular Dysfunction (pLVD) rather than norepinephrine. The aim of this study was to assess whether vasopressin is superior to norepinephrine to improve outcomes in patients with pLVD after cardiac surgery. Methods: This retrospective cohort study included 1, 156 patients with postoperative vasoplegic shock (mean arterial pressure <65 mmHg resistant to fluid challenge and cardiac index >2.20 L/min m 2 ) and pLVD (left ventricular ejection fraction ⩽35%, left ventricular end-diastolic diameter ≥60 mm, New York Heart Association ≥III) from 2007 to 2017. To address any indicated biases, we derived a propensity score predicting the functions of vasopressin (0.02–0.07 U/min) and norepinephrine (10–60 μg/min) on postoperative vasoplegic shock. The primary outcomes were 30-day mortality, mechanical ventilation more than 48 h, cardiac reoperation, extracorporeal membrane oxygenation, stroke, and acute kidney injury, whereas the secondary outcomes included infection, septic shock, atrial fibrillation and ventricular arrhythmias. Results: There were 338 patients (169 vasopressin and169 norepinephrine) with a similar risk profile in propensity score-matched cohort. In propensity-matched patients, the primary outcomes of vasopressin and norepinephrine showed no significant difference (50.89% vs. 58.58%, P = 0.155). However, compared with norepinephrine, secondary outcomes of vasopressin were increased due to the high rate of atrial fibrillation (11.83% vs. 20.12%, P = 0.038) and ventricular arrhythmias (14.20% vs. 24.85%, P = 0.014). Conclusions: Compared with norepinephrine, vasopressin could not improve the postoperative outcomes in patients with pLVD after cardiac surgery. Vasopressin should be cautious to be used as a first-line vasopressor agent in postcardiac vasoplegic shock. Abstract : Supplemental Digital Content is available in the text